Parasite-Host Interaction and Pathophysiology Studies of the Human Relapsing Malarias Plasmodium vivax and Plasmodium ovale Infections in Non-Human Primates - Pasini, Erica M.; Kocken, Clemens H. M. (Frontiers in Cellular and Infection Microbiology, 2021)
Malaria remains a serious health concern across the globe. Historically neglected, non-Falciparum human malarias were put back on the agenda by a paradigm shift in the fight against malaria from malaria control to malaria eradication. Here, we review the modeling of the relapsing parasites Plasmodium vivax (P. vivax) and Plasmodium ovale (P. ovale) in non-human primates with a specific focus on the contribution of these models to our current understanding of the factors that govern parasite-host interactions in P. vivax and P. ovale parasite biology and pathophysiology.